Analysis of Fixed Asset Accounting Treatment at PT. Wismilak Inti Makmur Tbk - Zul Sahyani Limbong; Renny Maisyarah (CV. ADMITECH SOLUTIONS, 2025)
This study aims to analyze the accounting treatment of fixed assets at PT Wismilak Inti Makmur Tbk in accordance with the applicable financial accounting standards in Indonesia, particularly PSAK No. 16 concerning Fixed Assets. Fixed assets play a crucial role in supporting the company’s operational activities, and their proper recognition, measurement, depreciation, and disclosure are essential for presenting fair and transparent financial reports. The research method used is a qualitative descriptive approach by examining the company’s financial statements, accounting policies, and related documentation. The study evaluates whether the company’s practices in acquisition, capitalization, depreciation methods, asset valuation, and disposal are consistent with the standards. The results indicate that PT Wismilak Inti Makmur Tbk has generally complied with PSAK No. 16 in the recognition and depreciation of its fixed assets. However, some aspects related to the reassessment of residual value and useful life estimation still require more regular review and documentation to enhance accuracy and transparency. Overall, the company's accounting treatment of fixed assets supports the reliability and comparability of its financial reporting.